Structured Oral Examinations in Internal Medicine - Case I - Hani Almoallim; Ali Alkatheeri; Alaa Monjed; Fozya Basheer; Abdullah Tawakol; Ahmad Imam; Abdulsalam Noorwali; Kamran Hameed (Association of American Medical Colleges, 2009)
Abstract This resource is one component of the nine-part Structured Oral Examinations in Internal Medicine series. In this case (Case I: Brain Abscess), a 50-year-old female is brought to the emergency room with complaints of fever, headache, and projectile vomiting for 5 days duration. She had a right ear surgery 2 weeks ago for chronic otitis media. She is hypertensive on ACE inhibitors. She works as a tailor. She is febrile with no meningeal signs. There is papilledema and left upper limb weakness. She has leukocytosis with space occupying lesion on a brain CT-scan. This approach of examination is very convenient to both students and examiners. It is structured and standardized. We were successfully able to avoid almost all disadvantages associated with a long case format. The majority of our students enjoyed the exam from personal and written feedback we received after the exam.